6y-10=-2(y+9)

Simple and best practice solution for 6y-10=-2(y+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-10=-2(y+9) equation:


Simplifying
6y + -10 = -2(y + 9)

Reorder the terms:
-10 + 6y = -2(y + 9)

Reorder the terms:
-10 + 6y = -2(9 + y)
-10 + 6y = (9 * -2 + y * -2)
-10 + 6y = (-18 + -2y)

Solving
-10 + 6y = -18 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-10 + 6y + 2y = -18 + -2y + 2y

Combine like terms: 6y + 2y = 8y
-10 + 8y = -18 + -2y + 2y

Combine like terms: -2y + 2y = 0
-10 + 8y = -18 + 0
-10 + 8y = -18

Add '10' to each side of the equation.
-10 + 10 + 8y = -18 + 10

Combine like terms: -10 + 10 = 0
0 + 8y = -18 + 10
8y = -18 + 10

Combine like terms: -18 + 10 = -8
8y = -8

Divide each side by '8'.
y = -1

Simplifying
y = -1

See similar equations:

| 4(4x-7)-8=4(x-4)+40 | | -4(-8+x)=20 | | U^2+u-42=0 | | (3x^2*y+y^2)dx+(3x^3-y^2+4xy)dy=0 | | 60-m=48 | | 27m=81 | | 3y-10+7y=20 | | 4m+3=40 | | u^2=64 | | -5x-19-2x-9=28 | | b-87=75 | | a+57=220 | | X-3x-5x=49 | | 9+6c-2c= | | xy(3x+2y)=4 | | 20=570+10x | | 11500*x=250000 | | 2y-10=12 | | 10000*x=250000 | | 20=(570-10x) | | 7+2(3x-1)=8x-3(2x+15) | | 33=5y-17 | | y-50=25 | | 0=r^2-282.24 | | 4+2p=10(3/5p-2) | | 7z+3=29(z-6) | | E^4x+5=6 | | 5v=72-3v | | 2y+3=7y-4 | | 15=x+16 | | 7/8=49/t | | 3(8-3m)-5m=10 |

Equations solver categories